The Dual Sample Aggregometer - Gerloff, J; von Kaulla, K. N (Thrombosis and Haemostasis, 1972)
An improved platelet aggregometer is described which permits the simultaneous recording of two aggregation curves obtained under technically strictly identical conditions which can be recorded with any single pen recorder. The curves are superimposed thus facilitating the visual or mathematical assessment of differences in the aggregation pattern. The instrument is particularly suitable for serial testing of aggregation inhibiting agents. It is equally suitable in the conventional way as any single channel aggregometer for routine testing of platelet aggregation.